Electron irradiation induced modifications of Ti(1-x)AlxN coatings and related buffer layers on steel substrates. (March 2021) - Weigel, Kai; Lu, Jun; Bewilogua, Klaus; Keunecke, Martin; Petersen, Jan; Grumbt, Gundis; Zenker, Rolf; Hultman, Lars
Abstract: Ti(1-x) Alx N hard coatings were prepared by reactive magnetron sputtering onto steel substrates (51CrV4 – 1.8159) and subsequently exposed for a short-time ( 1 s) to high-flux electron beam (EB) treatment. Morphology, composition and the structure of as-deposited and EB treated coatings were investigated using transmission electron microscopy (TEM), secondary ion mass spectroscopy (SIMS) and X-ray diffraction (XRD). It was found that the EB treatment had only a minor influence on the morphology and crystallinity of the Ti(1-x) Alx N phase, however, the stress-free lattice parameter and partly the compressive stress in the coatings were clearly reduced by the treatment. On the other hand, major changes of composition profiles and structure were observed in the metallic buffer layer between substrate and Ti(1-x) Alx N. The observed modifications in the coating-substrate system are explained by rapid heat up and radiation damage due to the fast electron exposure. Highlights: Ti(1-x) Alx N hard coatings and related buffer layers are markedly modified by electron beam treatment. Compositional and structural changes occur in the metallic buffer layer. Observed parameter modifications of the Ti(1-x)AlxN coatings after electron irridation are explained by a recovery model..